Phasic left atrial strain to predict worsening of diastolic function: Results from the prospective Berlin Female Risk Evaluation follow-up trial - Brand, Anna; Romero Dorta, Elena; Wolf, Adrian; Blaschke-Waluga, Daniela; Seeland, Ute; Crayen, Claudia; Bischoff, Sven; Mattig, Isabel; Dreger, Henryk; Stangl, Karl; Regitz-Zagrosek, Vera; Landmesser, Ulf; et al. (Frontiers in Cardiovascular Medicine, 2023)
Purpose The predictive value of maximum left atrial volume index (LAVI), phasic left atrial strain (LAS) and other standard echocardiographic parameters assessing left ventricular (LV) diastolic function to discriminate a future worsening of diastolic function (DD) in patients at risk is unclear. We aimed to prospectively assess and compare the clinical impact of these parameters in a randomly selected study sample of the general urban female population. Methods and results A comprehensive clinical and echocardiographic evaluation was performed in 256 participants of the Berlin Female Risk Evaluation (BEFRI) trial after a mean follow up time of 6.8 years. After an assessment of participants’ current DD status, the predictive impact of an impaired LAS on the course of DD was assessed and compared with LAVI and other DD parameters using receiver operating characteristic (ROC) curve and multivariate logistic regression analyses. Subjects with no DD (DD0) who showed a decline of diastolic function by the time of follow-up showed a reduced LA reservoir (LASr) and conduit strain (LAScd) compared to subjects who remained in the healthy range (LASr 28.0% ± 7.0 vs. 41.9% ± 8.5; LAScd −13.2% ± 5.1 vs. −25.4% ± 9.1; p < 0.001). With an area under the curve (AUC) of 0.88 (95%CI 0.82–0.94) and 0.84 (95%CI 0.79–0.89), LASr and LAScd exhibited the highest discriminative value in predicting worsening of diastolic function, whereas LAVI was only of limited prognostic value [AUC 0.63 (95%CI 0.54–0.73)]. In logistic regression analyses, LAS remained a significant predictor for a decline of diastolic function after controlling for clinical and standard echocardiographic DD parameters, indicating its incremental predictive value. Conclusion The analysis of phasic LAS may be useful to predict worsening of LV diastolic function in DD0 patients at risk for a future DD development. GRAPHICAL ABSTRACT